2003
DOI: 10.1007/s10072-003-0190-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term interferon-β treatment for multiple sclerosis

Abstract: The aim of our study was to analyze the dropout rate in patients with relapsing-remitting multiple sclerosis (RRMS) under long-term treatment with the three commercially available interferon beta (IFNbeta) preparations. According to the drug taken, we divided 122 RRMS patients into 4 groups: Betaferon group, 56 patients taking INFbeta-1b (24 MIU weekly, subcutaneous injections); Avonex group, 38 patients taking IFNbeta-1a (6 MIU weekly, intramuscularly); Rebif group, 18 patients taking INFbeta-1b (18 MIU subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 1 publication
4
42
1
1
Order By: Relevance
“…93 Treatment discontinuation of IFNβ therapies, regardless of cause, has been reported to be as high as 39.3% over 5 years in an observational study and 33.3% in a 6-year retrospective chart review. 93,94 Similar rates of discontinuation of glatiramer acetate for any reason have been reported. 95 No statistically significant differences have been found in the proportion of patients who discontinued treatment for any reason among IFNβ agents and glatiramer acetate.…”
Section: Factors Affecting Adherencesupporting
confidence: 57%
“…93 Treatment discontinuation of IFNβ therapies, regardless of cause, has been reported to be as high as 39.3% over 5 years in an observational study and 33.3% in a 6-year retrospective chart review. 93,94 Similar rates of discontinuation of glatiramer acetate for any reason have been reported. 95 No statistically significant differences have been found in the proportion of patients who discontinued treatment for any reason among IFNβ agents and glatiramer acetate.…”
Section: Factors Affecting Adherencesupporting
confidence: 57%
“…The discontinuation rate due to adverse events is variable among the available studies, with rates reported ranging from 14.7% to 58% [5][6][7]10,14]. In our population the discontinuation rate due to adverse events was relatively low (27.18%).…”
Section: Discussionmentioning
confidence: 57%
“…In the pivot clinical trials of this drugs, the rates of DMT persistence at the end of first year ranged from 90% to 97% [1][2][3][4]. However, these results may not be adequately extrapolated to the real world population, as lower rates of treatment persistence have been reported in post-marketing studies, with real-world studies describing rates of treatment persistence from 78.5% to 90% after one year and dropping to 59% to 72% between the third and fifth year of treatment, with discontinuation occurring mainly due to side effects and lack of efficacy [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 However, these medications may have downstream effects that include aching muscles, fever, and a host of other systemic post-injection reactions, often referred to as flu-like symptoms (FLS). 10,11 Adherence to therapy is increasingly recognized as critical to improving long-term outcomes in MS patients, yet long-term adherence rates for MS treatment rarely exceed 75%. 12 While convenience-related factors, such as dosing frequency, can affect adherence, 13 tolerability issues also represent an important potential barrier to adherence.…”
Section: Titrationmentioning
confidence: 99%